2008
DOI: 10.1111/j.1744-6163.2008.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Early and Accurate Diagnosis of Bipolar II Disorder Leads to Successful Outcomes

Abstract: The psychiatric advanced practice nurse contributes to successful treatment of bipolar II disorder through accurate diagnosis, evidence-based treatment, community referrals, coordination of care, professional organization participation, and patient advocacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, increased recognition of the high incidence of NDs in breast cancer patients among plastic surgeons may improve early recognition of these disorders. Prompt recognition with psychological referral as necessary may help reduce the impact these diagnoses have on patient outcomes [33][34][35] and resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased recognition of the high incidence of NDs in breast cancer patients among plastic surgeons may improve early recognition of these disorders. Prompt recognition with psychological referral as necessary may help reduce the impact these diagnoses have on patient outcomes [33][34][35] and resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Despite severe episodes being common, and with bipolar II disorder having the highest suicide rate of all psychiatric conditions [3], the prognosis is generally good following their formal diagnosis and administration of effective mood stabilizing medication [4 & ]. As a consequence, there have been a number of studies indicating that those with a bipolar disorder wait at least a decade from the onset of their mood episodes before they receive the correct diagnosis and diagnosis-specific treatment [9][10][11]12 The key risks associated with failure to diagnose a bipolar disorder include the inappropriate prescription of antidepressant drugs (as monotherapy) potentially worsening the illness course, failure to trial a mood stabilizer medication and the individual being misinformed about their particular mood condition. those that fail to meet duration or symptom number criteria), are under-recognised -with many patients having a bipolar disorder being diagnosed and managed as if they had a unipolar depressive condition.…”
Section: Introductionmentioning
confidence: 99%
“…In those diagnosed with a mood disorder, high proportional bipolar rates have been reported, with Angst and colleagues determining that, of those meeting DSM‐IV criteria for major depression, 16% met formal DSM criteria (and 47% met ‘softer’ criteria) for bipolar disorder. Despite such a distinct lifetime prevalence, clinical detection is often poor, with several studies (e.g., ) finding intervals from onset to formal diagnosis (for those so diagnosed) of a decade or longer, and up to twice the delay in those with a BP‐II diagnosis as against a BP‐I diagnosis . As it is commonly suggested that those with bipolar disorder require differing management strategies from those with unipolar disorder (i.e., most commonly mood‐stabilizing drugs, and with antidepressant drugs recognized as risking worsening the illness course), and that management rules for BP‐II should not necessarily be extrapolated from managing BP‐I , there is a logical requirement for accurate detection, diagnosis, and disorder‐nuanced management strategies.…”
mentioning
confidence: 99%